The Effect of Saliva with Different Nitrogen Compositions on Ruminal Fermentation in a Rumen Simulator Technique (Rusitec®) System Fed a Lactating Dairy Cow Diet - Ícaro Rainyer Rodrigues de Castro; Luiza de Nazaré Carneiro da Silva; Isabela Fonseca Carrari; Giulia Berzoini Costa Leite; Eduardo Marostegan de Paula; Amanda Moelemberg Cezar; Marcos Inácio Marcondes (Fermentation, 2025)
In vitro methods have advanced research on rumen microbiology and fermentation. However, artificial saliva formulation may need adjustments, particularly in urea content, for modern diets, warranting further research. This study investigated the effects of different nitrogen (N) levels in artificial saliva on ruminal fermentation and digestion in diets for dairy cows using a Rusitec® system. Eighteen fermenters tested three saliva treatments with different N levels: a standard saliva as the control and two treatments with N reduced by 15% and 30%. Data were analyzed as a completely randomized design using the MIXED procedure of SAS (v. 9.4), with linear and quadratic contrasts tested for treatment effects (significance set at p ≤ 0.05). Results showed that altering N content had no significant effect on pH, ammonia concentrations, or NH3-N outflow, nutrient digestibility (dry matter, crude protein, fiber, and starch), gas and methane production, or volatile fatty acid concentrations. The efficiency of microbial protein synthesis and N flow exhibited quadratic responses, with the lowest values observed at the highest level of N reduction in the saliva (−30%). These findings suggest that although ruminal function and digestion remain stable with reduced N, microbial protein synthesis efficiency may decline beyond a threshold.